Hyperoxemia Is Associated With Mortality in Critically Ill Children - Pelletier, Jonathan H.; Ramgopal, Sriram; Horvat, Christopher M. (Frontiers in Medicine, 2021)
Multiple studies among adults have suggested a non-linear relationship between arterial partial pressure of oxygen (PaO2) and clinical outcomes. Meta-analyses in this population suggest that high levels of supplemental oxygen resulting in hyperoxia are associated with mortality. This mini-review focuses on the non-neonatal pediatric literature examining the relationship between PaO2 and mortality. While only one pilot pediatric randomized-controlled trials exists, over the past decade, there have been at least eleven observational studies examining the relationship between PaO2 values and mortality in critically ill children. These analyses of mixed-case pediatric ICU populations have generally reported a parabolic (“u-shaped”) relationship between PaO2 and mortality, similar to that seen in the adult literature. However, the estimates of the point at which hyperoxemia becomes deleterious have varied widely (300–550 mmHg). Where attempted, this effect has been robust to analyses restricted to the first PaO2 value obtained, those obtained within 24 h of admission, anytime during admission, and the number of hyperoxemic blood gases over time. These findings have also been noted when using various methods of risk-adjustment (accounting for severity of illness scores or complex chronic conditions). Similar relationships were found in the majority of studies restricted to patients undergoing care after cardiac arrest. Taken together, the majority of the literature suggests that there is a robust parabolic relationship between PaO2 and risk-adjusted pediatric ICU mortality, but that the exact threshold at which hyperoxemia becomes deleterious is unclear, and likely beyond the typical target value for most clinical indications. Findings suggest that clinicians should remain judicious and thoughtful in the use of supplemental oxygen therapy in critically ill children.